2023
DOI: 10.5194/gmd-16-383-2023
|View full text |Cite
|
Sign up to set email alerts
|

The tidal effects in the Finite-volumE Sea ice–Ocean Model (FESOM2.1): a comparison between parameterised tidal mixing and explicit tidal forcing

Abstract: Abstract. Tides are proved to have a significant effect on the ocean and climate. Previous modelling research either adds a tidal mixing parameterisation or an explicit tidal forcing to the ocean models. However, no research compares the two approaches in the same framework. Here we implement both schemes in a general ocean circulation model and assess both methods by comparing the results. The aspects for comparison involve hydrography, sea ice, meridional overturning circulation (MOC), vertical diffusivity, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Since the seminal work of Munk (1966), great efforts have been made to understand what controls diapycnal mixing in the ocean interior (e.g., MacKinnon et al., 2017; Munk & Wunsch, 1998; St. Laurent & Garrett, 2002) and to refine the parameterizations of vertical diffusivity in ocean general circulation models (GCM) (e.g., Bryan & Lewis, 1979; de Lavergne et al., 2020; Gargett, 1984; Jayne, 2009; Melet et al., 2016; Saenko & Merryfield, 2005; Schmittner & Egbert, 2014; Simmons et al., 2004; Song et al., 2023). Recent work has comprehensively reviewed what is currently known about the role of ocean mixing in the climate system (de Lavergne et al., 2022; Melet et al., 2022; Whalen et al., 2020) and, in particular, the contribution of different internal wave processes (e.g., near‐field and far‐field internal tide dissipation, lee wave dissipation and wind‐induced near‐inertial wave energy dissipation) to the total mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal work of Munk (1966), great efforts have been made to understand what controls diapycnal mixing in the ocean interior (e.g., MacKinnon et al., 2017; Munk & Wunsch, 1998; St. Laurent & Garrett, 2002) and to refine the parameterizations of vertical diffusivity in ocean general circulation models (GCM) (e.g., Bryan & Lewis, 1979; de Lavergne et al., 2020; Gargett, 1984; Jayne, 2009; Melet et al., 2016; Saenko & Merryfield, 2005; Schmittner & Egbert, 2014; Simmons et al., 2004; Song et al., 2023). Recent work has comprehensively reviewed what is currently known about the role of ocean mixing in the climate system (de Lavergne et al., 2022; Melet et al., 2022; Whalen et al., 2020) and, in particular, the contribution of different internal wave processes (e.g., near‐field and far‐field internal tide dissipation, lee wave dissipation and wind‐induced near‐inertial wave energy dissipation) to the total mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in fidelity resulting from the inclusion of tidal forcing in OGCMs have also been found outside ice-covered regions. Song et al (2023) compared global implementations of the Finite-volumE Sea ice-Ocean Model (FESOM2.1) with and without explicit tidal forcing, concluding that tides strengthened both the upper and lower cells of the global overturning circulation, as well as the Antarctic Circumpolar Current (ACC). Katavouta et al (2022) reported a marked improvement in the representation of critical water masses in a regional 1/12 • model of the Indonesian Archipelago when tides were present.…”
Section: Introductionmentioning
confidence: 99%